A Framework for Analyzing the Economic Tradeoffs Between Urban Commerce and Security Against Terrorism. Issue 8 (7th April 2014) - Rose, Adam; Avetisyan, Misak; Chatterjee, Samrat
<x xml:space="preserve">Abstract</x> This article presents a framework for economic consequence analysis of terrorism countermeasures. It specifies major categories of direct and indirect costs, benefits, spillover effects, and transfer payments that must be estimated in a comprehensive assessment. It develops a spreadsheet tool for data collection, storage, and refinement, as well as estimation of the various components of the necessary economic accounts. It also illustrates the usefulness of the framework in the first assessment of the tradeoffs between enhanced security and changes in commercial activity in an urban area, with explicit attention to the role of spillover effects. The article also contributes a practical user interface to the model for emergency managers.